Digitalization of Marketing, Finance and Inventory Management in MSMEs “Sriti Gamplong” - Audita Nuvriasari; Bhakti, Listiana; Fadhila, Annisa Nur; Asmarani, Widya Puspita; Pramudian, Achmad Fajri; Raihan, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service activity is carried out by the MSMEs